1989
DOI: 10.1093/jac/24.suppl_a.169
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal activity of meropenem against Pseudomonas aeruginosa

Abstract: Ten strains of Pseudomonas aeruginosa that were susceptible to imipenem (MICs 2 mg/l) were exposed to a new parenteral carbapenem, meropenem (MIC 0.25 mg/l). Kinetic turbidometry showed that, as with other beta-lactam antibiotics, there was a prelytic increase in the culture OD following exposure to meropenem. The maximal value of the prelytic increase in the OD was higher for meropenem than for imipenem at concentrations 0.5, 1, 2, 4 and 8 x MIC. This corresponded to the formation of short filaments during ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
3
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…␤-Lactams are not considered to display concentration-dependent activity; however, this usually refers to activity at concentrations above the MIC. This study verifies the findings of others which demonstrated concentration-dependent activity of imipenem and meropenem over a range of concentrations (5,21). For both drugs, concentrations of Ն4 times the MIC resulted in killing of 3 log units that was maintained for 24 h. In contrast, Flukiger et al (6) observed no concentrationdependent killing by imipenem of P. aeruginosa when comparing concentrations of 2 and 10 times the MIC.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…␤-Lactams are not considered to display concentration-dependent activity; however, this usually refers to activity at concentrations above the MIC. This study verifies the findings of others which demonstrated concentration-dependent activity of imipenem and meropenem over a range of concentrations (5,21). For both drugs, concentrations of Ն4 times the MIC resulted in killing of 3 log units that was maintained for 24 h. In contrast, Flukiger et al (6) observed no concentrationdependent killing by imipenem of P. aeruginosa when comparing concentrations of 2 and 10 times the MIC.…”
Section: Discussionsupporting
confidence: 90%
“…These concentration-dependent effects on regrowth were verified by the spectrophotometric analysis. Other investigators have demonstrated effects of carbapenems at concentrations below the MIC (15,21). Our findings were similar, with demonstrable concentration-dependent activity at concentration/MIC ratios of as low as 0.25 times the MIC for both agents.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This phenomenon suggests that meropenem has different target-binding affinities and/or route or access through the outer membrane of this bacterial species [7]. For Pseudomonas aeruginosa we have previ ously showed also a lag of 2 h in killing for meropenem [11].…”
Section: Discussionmentioning
confidence: 91%
“…Several attempts have been made to compensate for this effect. (i) The antimicrobial activity of constant concentrations of antibiotics may be examined in a static system in which the bacterial culture is not diluted during the investigation (12). (ii) Dynamic in vitro models which do not allow bacteria to be washed out have been developed (1,2).…”
mentioning
confidence: 99%